Disentangling the ecological basis of floral trait variation in Neotropical Piper species - Valentin-Silva, Adriano [UNESP] (2021)
In generalist pollination systems, it has been assumed that pollinators play a minor role in the diversification of floral traits, but recent studies have pointed to a different scenario. Although pollination in Piper is considered generalist, there are flower and inflorescence variations among subclades that may be associated with different pollinator functional groups. Based on this, we aimed to test whether pollinators influenced the evolution of floral traits in a clade of generalist plants, by studying 17 co-occurring Piper spp. Sixteen species were insect-pollinated (46 species: bees, beetles and flies). We found no evidence of anemophily. Eight species were dependent on pollen vectors for sexual reproduction, but no correlation between floral and pollinator traits was recorded. None of the floral traits presented phylogenetic signal, and the evolution of these traits was not correlated. Nine species were independent of pollen vectors for sexual reproduction. We did not find any evidence of pollinator-driven floral diversification of Piper spp.; we suggest a possible role of abiotic factors as agents of selection on floral diversification. As self-pollination seems to be a common feature in the genus, the flexibility of mating systems could be another important factor related to the maintenance of floral phenotypic variation.